Trends in the abundance of Celtic Sea demersal fish: Identifying the relative importance of fishing and environmental drivers - Kempf, Jed; Breen, Patricia; Rogan, Emer; Reid, David G. (Frontiers in Marine Science, 2022)
The Celtic Sea is a productive fishing ground, therefore identifying the relative importance of fishing and environmental factors on fish stock dynamics is crucial for developing our understanding of sustainable yields and to operationalize Ecosystem Based Fisheries Management (EBFM). We investigated the effect of environmental variables and fishing on the relative abundance inferred from catch-per-unit-effort (CPUE), of twelve demersal stocks (i.e., cod, haddock, whiting, anglerfish, hake, megrim, plaice, sole, lesser-spotted dogfish, spurdog, Trisopterus spp., skates and rays) in the Celtic Sea from 1997 to 2019 (23 years). Annualized time series (1997-2019) of net primary production, bottom temperature, copepod abundance (Calanus finmarchicus and Calanus helgolandicus) and North Atlantic Oscillation index were used to characterize key environmental variables. Fishing exploitation rates (F/FMSY) were used to represent fishing pressure and CPUE trends derived from an International Bottom Trawl Survey (IBTS) were used to infer abundance. We used redundancy analysis to identify key explanatory variables and then dynamic factor analysis to assess their relationships with the CPUE series and identify underlying patterns in the unexplained temporal variation. Our results show that for the majority of demersal fish species, the CPUE trends were strongly influenced by fishing exploitation rates. The gradual reduction in exploitation rates observed throughout the study period most likely led to the partial recovery of cod, spurdog, hake, megrim, plaice, whiting, Trisopterus spp., and the skates and rays. In addition, exploitation patterns on one stock influenced CPUE trends of other demersal stocks (e.g., hake, megrim, plaice, lesser-spotted dogfish, sole). We also observed that the CPUE of whiting, hake and plaice increased when C. finmarchicus were abundant in the plankton. We infer from our findings in the investigated time series that the recovery of cod, spurdog, hake, megrim, plaice, whiting, Trisopterus spp., and the skates and rays in the Celtic Sea remains dependent on controlling fishing mortality, and this would not, at least for now, be confounded by the environmental conditions.